Focal adhesion in the tumour metastasis: from molecular mechanisms to therapeutic targets - Zonghao Liu; Xiaofang Zhang; Tianru Ben; Mo Li; Yi Jin; Tianlu Wang; Yingqiu Song (Biomarker Research, 2025)
Abstract The tumour microenvironment is the “hotbed” of tumour cells, providing abundant extracellular support for growth and metastasis. However, the tumour microenvironment is not static and is constantly remodelled by a variety of cellular components, including tumour cells, through mechanical, biological and chemical means to promote metastasis. Focal adhesion plays an important role in cell-extracellular matrix adhesion. An in-depth exploration of the role of focal adhesion in tumour metastasis, especially their contribution at the biomechanical level, is an important direction of current research. In this review, we first summarize the assembly of focal adhesions and explore their kinetics in tumour cells. Then, we describe in detail the role of focal adhesion in various stages of tumour metastasis, especially its key functions in cell migration, invasion, and matrix remodelling. Finally, we describe the anti-tumour strategies targeting focal adhesion and the current progress in the development of some inhibitors against focal adhesion proteins. In this paper, we summarize for the first time that focal adhesion play a positive feedback role in pro-tumour metastatic matrix remodelling by summarizing the five processes of focal adhesion assembly in a multidimensional way. It is beneficial for researchers to have a deeper understanding of the role of focal adhesion in the biological behaviour of tumour metastasis and the potential of focal adhesion as a therapeutic target, providing new ideas for the prevention and treatment of metastases.